THE EFFECT OF YIELD STRUCTURE ELEMENTS ON SPRING BARLEY (HORDEUM VULGARE L.) PRODUCTIVITY IN THE ENVIRONMENTS OF RUSSIA’S EXTREME NORTH - O. B. Batakova; V. A. Korelina (Труды по прикладной ботанике, генетике и селекции)
Yield structure elements of four productive accessions have been studied in the competitive variety testing nursery at Arkhangelsk Research Institute of Agriculture. Correlation analysis has been carried out between productivity, growing season, and yield structure elements. Priority elements of yield structure in the Extreme North environments are: productive tillering, 1000 grain weight, and ear length. An important factor is the duration of the growing season which correlates directly with productivity.